Water vapor permeability and self‐cleaning properties of solvent‐free polyurethane improved by hollow nano‐TiO2 spheres. Issue 1 (17th July 2020) - Guo, Xu; Lyu, Bin; Gao, Dangge; Cheng, Kun; Ma, Jianzhong; Yang, Na; Yu, Yajin; Zhao, Shunhua; Shi, Lei; Kou, Mengnan
Abstract: In the synthetic leather industry, solvent‐free polyurethane film (SFPU) was poor in water vapor permeability (WVP) and washability. In this study, we introduced the hollow nano‐TiO2 spheres (HNTSs) with high photocatalytic performance and permeability performance as well as large surface area into the SFPU film to endued its superior water vapor permeability property, self‐cleaning performance and water resistance. First of all, HNTSs were prepared via the controllable chemical route using HF for internal corrosion of solid nano‐TiO2 spheres, and then introduced into hydroxyl prepolymer to prepare solvent‐free polyurethane/HNTSs composite film. The results of SEM, FT‐IR and UV analyses indicated HNTSs were successfully dispersed evenly into SFPU. Application experiment results showed that the addition of HNTSs with hollow structure had an important effect on the WVP, photocatalytic performance, mechanical property, the water vapor transmission rate, self‐cleaning performance as well as tensile strength were increased by 111.98%, more than 100%, and 36.368%, respectively. Abstract : The hollow nano‐TiO2 spheres significantly improve the self‐cleaning performance and water vapor permeability of the composite film. This work is expected to promote the development of the synthetic leather industry and reduce the usage of detergents.